CRIX or evaluating blockchain based currencies - Wolfgang Karl Härdle; Simon Trimborn (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
More and more companies start offering digital payment systems. Smartphones evolve to a digital wallet such that it seems like we are about to enter the era of digital finance. In fact we are already inside an digital economy. The market of e-x (x = "finance", "money", "book", you name it ... ) has not only picked up enormous momentum but has become standard for driving innovative activities of the global economy. A few clicks at y and payment at z brings our purchase to location w. Own currencies for the digital market were therefore just a matter of time. The idea of the Nobel Laureate Hayek, see [1], to let companies offer concurrent currencies seemed for a long time scarcely probabilistic, but the invention of the Blockchain made it possible to fill his vision with life. Cryptocurrencies (abbr. cryptos) came up and widened the angle towards this new level of economic interaction. Since bitcoins' appearance a bunch of new cryptos spread the web and offered new ways of proliferation. The crypto market then fanned out and showed clear signs of acceptance and deep liquidity so that one has to look closer at the general moves and dynamics.
Keywords: C51; C52; G10; 330; index construction; CRIX; risk analysis; bitcoin; cryptocurrency